(untitled) (Gestão & Regionalidade, 2024)
This paper assesses the correlation between socioeconomic and demographic variables with the perceptions of individuals about retirement.Using data from the "Raio X do investidor" a survey conducted by the Brazilian Association of Financial and Capital Markets Entities (ANBIMA) in partnership with DataFolha. We use descriptive analysis and logistic regression to study about retirement that capture different issues as a dependent variable, such as strategy, expected standard of living, and age that individuals intend to retire. Our main results suggest that genders have different perceptions about retirement. The study also reinforces that individuals with lower education and income levels are more likely to choose the INSS as a strategy. The findings reinforce the existing inequalities in the country, being useful for political agents and future strategies of social security evaluation. This research contributes to complement personal finance studies, such as Potrich, Vieira & Kirch (2015), innovating with a focus on retirement.